Use of OPAC As A Means Of Refinding Information On STMIK Pelita Nusantara Library: Use of OPAC As A Means Of Refinding Information On STMIK Pelita Nusantara Library - Jonson Manurung (Institute of Computer Science (IOCS), 2020)
The development of Information Technology (IT) which is so fast lately, has an impact on services in the library. Library is an institution that plays a role in collecting, processing and distributing information which prioritizes search engines as a means of retrieving information. The rapid development of technology has made us co-exist with information technology itself. Now many library users have started to abandon the manual method of searching for information that takes a long time in the search process, and switch to using the Information Retrieval System that is on the network. Catalogs for some people are obsolete objects that are rarely used for information retrieval, but along with technological developments, online catalogs are now available that can be accessed via electronic devices, such as computers or smartphones called OPAC (Online Public Access Catalog). The impact is if there is no information retrieval system (OPAC), then searching for documents in the library will be more difficult because users have to browse directly to the shelf without first searching the OPAC. The Library of STMIK Pelita Nusantara is one of the higher education libraries in Medan, where the library information data collection is still manual, namely library users who come, often directly looking for collections on the shelf, or by asking library staff for help to find the desired book. From the background of the problem above, the writer is interested in taking the title of research on the Use of OPAC as a Means of Retrieving Information in the Library of STMIK Pelita Nusantara.